A companion to Ancient near Eastern art - Gunter, Ann Clyburn (Blackwell Companions to the Ancient World Ser, 2018)
Intro -- Table of Contents -- Preface -- CHAPTER ONE: The "Art" of the "Ancient Near East" -- Introduction -- Defining the "Ancient Near East" -- Periodization and Chronology of the "Ancient" Near East -- Modern Frameworks for an "Ancient Near Eastern Art" -- Did the Ancient Near East in Fact Produce "Art"? -- Comparative Approaches -- Conclusions -- GUIDE TO FURTHER READING -- REFERENCES -- PART I: APPROACHES AND METHODS OF ANALYSIS AND INTERPRETATION -- CHAPTER TWO: Art and Material Culture -- Introduction -- The Mechanical Reproduction of Images -- Art, Material Culture, and Social Scale -- The "Bureaucratic Eye" -- Image, Commerce, and Cosmology -- Cult Images and the Mixture of Materials -- Conclusion -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER THREE: Meaning and Interpretation -- Introduction -- New Perspectives from Anthropology and History -- The Methods of Art History and the Ancient Near East -- Text and Image -- The "Fribourg School": The Bible and Ancient Near Eastern Iconography -- The Purpose and Persistence of Images -- Missing "Images" and Their Interpretation -- Conclusion -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER FOUR: Style -- Introduction -- Challenges of Style for the Study of Ancient Near Eastern Art -- Potentials of Stylistic Analysis, I: Selected Examples from Ancient Near Eastern Art -- Potentials of Stylistic Analysis, II: Ancient Near Eastern Glyptic -- Seal Styles and the Achaemenid Empire (ca. 550-330 BCE) -- Conclusion -- GUIDE TO FURTHER READING -- REFERENCES -- CHAPTER FIVE: Connoisseurship and Classification -- Introduction: Issues of Terminology -- Connoisseurship and Classification -- Connoisseurship, Classification, and Style: Passive Reflection of Normative Rules to Means of Active Communication and Information Exchange